1998
DOI: 10.1063/1.166367
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of cellular automaton pairs

Abstract: The phenomenon of synchronization in pairs of cellular automata coupled in a driver-replica mode is studied. Necessary and sufficient conditions for synchronization in linear cellular automaton pairs are given. The couplings that make a pair synchronize are determined for all linear elementary cellular automata. (c) 1998 American Institute of Physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In Ref. [6] it was shown that a pair of ECAs that evolve using the local rule 90, synchronize if the coupled coordinates are separated by a block of N = 2 n -1 decoupled sites, where n is a positive integer. Based on the phenomenon of synchronization, in Ref.…”
Section: Cellular Automatamentioning
confidence: 99%
“…In Ref. [6] it was shown that a pair of ECAs that evolve using the local rule 90, synchronize if the coupled coordinates are separated by a block of N = 2 n -1 decoupled sites, where n is a positive integer. Based on the phenomenon of synchronization, in Ref.…”
Section: Cellular Automatamentioning
confidence: 99%
“…In this work is considered the encryption scheme used in [9], where the synchronization phenomenon of cellular automata has been applied to design two families of permutations Ψ and Φ, and an asymptotically perfect pseudo-random number generator. This cryptosystem is flexible and reconfigurable for different bit-lengths.…”
Section: Encryption System Escamentioning
confidence: 99%
“…The encryption system considered in this implementation is based on the synchronization of the cellular automaton rule 90 [9]. This cryptosystem is named ESCA (for short) and it has been validated and implemented for image encryption in [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of coupling is handled by means of a probability, and numerical evidence in several examples supports the existence of a critical value of the probability above which the pair synchronizes identically. The other form is a deterministic coupling as was done in [10]. Therein, necessary and sufficient conditions for synchronization of coupled affine elementary cellular automata were given.…”
mentioning
confidence: 99%
“…Therein, necessary and sufficient conditions for synchronization of coupled affine elementary cellular automata were given. The proof in [10] is based on the existence of a connection between synchronization and nilpotency of matrices. The natural generalization of that approach led us to the study of the nilpotency of a broader class of matrices.…”
mentioning
confidence: 99%